Benefit of industrial education for girls - Paddleford, Hattie A. (My University, 1896)
Introduction: An industrial education should mean a thorough preparation for some special form of manual labor. Formerly the system of apprenticeship afforded ample means for the boys to obtain such an education, but even this kind of an education for an industrial training has fallen into disuse. The states are providing for this deficiency by establishing agricultural colleges, and in a great many of them, girls are admitted, others are being opened up to them, and perhaps in time, all will be open. In some of them the girls receive a thorough training in agricultural lives.
Citation: Paddleford, Hattie A. Benefit of industrial education for girls. Senior thesis, Kansas State Agricultural College, 1896.
Morse Department of Special Collections
Keywords: Industrial education; Manual labor; Agricultural colleges; Theses; Manuscripts (documents)